2013
DOI: 10.1007/s11241-013-9190-4
|View full text |Cite
|
Sign up to set email alerts
|

Fair lateness scheduling: reducing maximum lateness in G-EDF-like scheduling

Abstract: Existing research in soft real-time scheduling has focused on determining tardiness bounds given a scheduling algorithm. In this paper, we study lateness bounds, which are related to tardiness bounds, and propose a scheduling algorithm to minimize lateness bounds, namely the global fair lateness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…The most well-known window-constrained algorithm is G-EDF, which uses the deadline of each job as its PP. However, Erickson et al [9] demonstrated that allowing PPs set earlier than deadlines can result in better response-time bounds. The G-FL scheduler, mentioned in Sec.…”
Section: Determining End-to-end Latencymentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-known window-constrained algorithm is G-EDF, which uses the deadline of each job as its PP. However, Erickson et al [9] demonstrated that allowing PPs set earlier than deadlines can result in better response-time bounds. The G-FL scheduler, mentioned in Sec.…”
Section: Determining End-to-end Latencymentioning
confidence: 99%
“…Recently, Erickson et al showed that "G-EDF-like" (GEL) schedulers, such as the global fair-lateness (G-FL) scheduler, have provably smaller response-time bounds than G-EDF [9]. Under GEL schedulers, priority points (PPs) distinct from deadlines are defined to minimize worst-case response times.…”
Section: Introductionmentioning
confidence: 99%
“…An improved, but more complex, bound was introduced in [9]. While these works focused on G-EDF itself, [8] proposed G-FL as a new scheduler with analysis similar to G-EDF in [9]. G-FL usually provides a smaller maximum lateness bound for the task system.…”
Section: Tardiness Boundsmentioning
confidence: 99%
“…One of the advantages of G-FL promoted in [8] is that it is a job-level static priority (JLSP) algorithm, which is important for synchronization mechanisms such as those discussed in [3]. However, when splitting is introduced, the algorithm is no longer truly JLSP.…”
Section: Handling Critical Sectionsmentioning
confidence: 99%
See 1 more Smart Citation